Formation of CuInSe2 and CuGaSe2 Thin‐Films Deposited by Three‐Stage Thermal Co‐Evaporation: A Real‐Time X‐Ray Diffraction and Fluorescence Study. Issue 10 (26th June 2013) - Rodriguez‐Alvarez, Humberto; Weber, Alfons; Lauche, Jakob; Kaufmann, Christian Alexander; Rissom, Thorsten; Greiner, Dieter; Klaus, Manuela; Unold, Thomas; Genzel, Christoph; Schock, Hans‐Werner; Mainz, Roland
Abstract Thin film solar cells based on co‐evaporated Cu(In, Ga)Se2 absorber films present the highest efficiencies among current polycrystalline thin‐film technologies. Thanks to the development of a novel experimental setup for in situ growth studies, it was possible to follow the formation of the crystalline phases during such deposition processes for the first time. This synchrotron‐based energy‐dispersive X‐ray diffraction and fluorescence setup is suited for real‐time studies of thin film vapor deposition processes. Focusing on the growth of CuInSe2 and CuGaSe2 fabricated by three‐stage processing, we find that the phase transitions in the Cu‐In‐Se system follow the reported pseudo‐binary In2Se3‐Cu2Se phase diagram. This requires a transformation of the Se sublattice during the incorporation of Cu‐Se into the In2Se3 precursor film from the first process stage. In the Cu‐Ga‐Se system, besides an increase in the lattice spacings, we observe no transformation of the Se sublattice. Furthermore, the structural defects of the Ga‐Se precursor film are preserved until the CuGaSe2 stoichiometry is reached. By means of model calculations of the fluorescence signals, we confirm in both systems the segregation of Cu2Se at the surface near a concentration of 25 at.% Cu shortly after the recrystallization of the films. The modeling also reveals that Cu2Se penetrates into the CuInSe2 film, whereas it remains at the surface of the CuGaSe2 film.